Thrust force prediction of twist drill tools using a 3D CAD system application programming interface. (27th June 2011) - Kyratsis, Panagiotis; Tapoglou, Nikolaos; Bilalis, Nikolaos; Antoniadis, Aristomenis
Twist drills are geometrical complex tools and various researchers have adopted different mathematical and experimental approaches for their simulation. The present paper acknowledges the increasing use of modern CAD systems and subsequently, using the application programming interface (API) of a typical CAD system, drilling simulations are carried out. The developed DRILL3D software routine, creates, via specifying parameters, tool geometries, so that using different cutting conditions, realistic solid models are produced incorporating all the relevant data involved. The 3D solid models of the undeformed chips coming from both cutting areas are segmented into smaller pieces, in order to calculate every primitive thrust force component involved with high accuracy. The resultant thrust force produced, is verified by adequate amount of experiments using a number of different tools, speeds and feed rates. The final data derived consist of a platform for further direct simulations regarding the determination of tool wear, drilling optimisations etc.